Shallow geothermal energy for industrial applications: A case study. (August 2016) - Focaccia, S.; Tinti, F.; Monti, F.; Amidei, S.; Bruno, R.
Highlights: Geothermal pumps may be adapted to supply process heat to industrial applications. Combination of geostatistical and numerical simulation decreases the risk of failure. Thermal energy storage is an added value in shallow geothermal projects. Thermal energy storage decreases the risk of failure for industrial projects. EGPT process can benefit from the use of shallow geothermal energy. Abstract: Shallow geothermal energy is of great interest for HVAC (heating, ventilation and air conditioning) designers. While increasingly popular in the residential and commercial sectors, shallow applications are still little used in the industrial sector and unfamiliar to policy makers, designers and stakeholders [1]. Despite this, geothermal applications are feasible for industrial plant for several reasons: operating at high load factors and supplying energy to a single location, geothermal systems would cut energy costs, a large slice of overall industrial production costs. This paper presents the results of a feasibility study carried out for an industrial shallow geothermal project, where the required preheating to the innovative Expanding-Gas-Power-Transformation (EGPT) process was supplied through a Hybrid Geothermal-Air Transcritical Heat Pump. Focus was given to modeling the geothermal component to comply with the heat pump working temperature requirements, integrating this with geostatistics and numerical simulation of heat/water flows.